Mathematical substantiation of the method for assessing the risk of progression of diabetic retinopathy with serum leptin determination in patients with metabolic syndrome and diabetes mellitus (Ukrainian Journal of Ophthalmology, 2026)
Background: Issues of not only the development of methods for treatment of diabetic retinopathy (DR), but also search for criteria reflecting the development and risk for progression of the disease in type 2 diabetes mellitus (T2DM), particularly in the presence of metabolic syndrome (MS)) have been actively addressed in the literature.Purpose: To improve the approach to diagnosis of DR in the presence of MS through the development of a mathematical algorithm for determining the nature of the development and the risk for progression of DR taking into account serum leptin levels.Materials and Methods: One hundred and three patients (187 eyes) with MS, T2DM and DR (men and women; mean age, 59.49±0.92 years; mean diabetes duration, 10.12±0.86 years; mean HbA1C,  9.10±0.19 %; mean body mass index (BMI), 33.00±0.64 kg/m2), were involved in the study. The diagnostic accuracy and predictive value of serum leptin determination were assessed by discriminant analysis. Models with linear combinations of the serum leptin, low density lipoprotein cholesterol (LDLC), triglyceride (TG), HbA1C,  type of anti-hyperglycemic therapy (oral anti-hyperglycemic medication or insulin therapy) were developed, and, subsequently, formulas for classification-relevant discriminant functions were derived.Results: The formulas for classification-relevant discriminant functions were derived based on the results of physical examination, imaging and laboratory tests, and subsequent assessment of clinical signs of T2DM (HbA1C), MS (LDLC, TG and leptin) and DR stage, and taking into account the type of anti-hyperglycemic therapy. Using the formulas, one can determine the probability of progression or stabilization of DR. The use of the algorithm assessing the prediction of the development of DR made it possible to predict stabilization of the course of DR in the majority (57.7%) of cases. Of these, 38.25%, 38.25%, and 23.5% were at stage 1 DR, stage 2 DR and stage 3 DR, respectively (р=0.02 or р=0.01, depending on the type of mathematical model).Conclusion: We described a new technique for assessing the risk for progression of DR in patients with both T2DM and MS, taking into account serum leptin levels, with the informativeness of 67.8% or 68.9%.
Keywords: diabetic retinopathy; metabolic syndrome; leptin